Does sugammadex decrease the severity of agitation and complications in pediatric patients undergoing adenotonsillectomy? - Korkmaz, Muge O. (Saudi Med J, 2019)
OBJECTIVES: To evaluate the effectiveness of sugammadex in reducing or eliminating postoperative agitation levels, early respiratory complications and nausea/vomiting in children undergoing adenotonsillectomy. METHODS: A total of 70 patients (age range: 5-13 years) who underwent an adenotonsillectomy in the Otolaryngology Clinic, Sakarya University, Sakarya, Turkey between May 2015 and September 2017 were included in the study. The patients were randomized into a sugammadex group (Group S) and a neostigmine + atropine (Group N); each group contained 35 patients. Time to extubation, postoperative agitation levels, and early postoperative complications were evaluated and recorded. Data from both groups were statistically evaluated and compared. RESULTS: The time to extubation was significantly shorter in Group S than Group N (p<0.05). Agitation scores during recovery were significantly lower in Group S than Group N (p<0.05). More complications were observed in Group N than in Group S; the number of patients seen coughing and experiencing nausea/vomiting in Group S was statistically significantly lower (p<0.05). CONCLUSION: This study demonstrated that the use of sugammadex results in less time to recovery and less agitation in comparison to conventional administration of neostigmine + atropine in the reversal of neuromuscular blocking after adenotonsillectomy.